Seroprevalence of hepatitis B and C viruses in the province of Tokat in the Black Sea region of Turkey: A population-based study - Beytullah YILDIRIM; Şener BARUT; Yunus BULUT; Gülgün YENİŞEHİRLİ and Metin ÖZDEMİR and; n ÇETİN and Ali AKBAŞ and Ömer ATIŞ and Hüseyin ÖZYURT and Şemsettin ŞAHİN (Turkish Journal of Gastroenterology, 2019)
-